Bridging the gap between ESP theory and classroom practice: A study of vocational school teachers’ knowledge, attitudes, and instructional practices - Mochamad Imron Azami; Fitri Awaliyatush Sholihah (Englisia: Journal of Language, Education, and Humanities, 2026)
English for Specific Purposes (ESP) in vocational education has been considered as an essential requirement however, it is not consistently practiced within the classroom. In this context, the study explores Vocational English teachers’ conceptual awareness of ESP as well as their pedagogical understanding, orientation and practice concerning its implementation. A quantitative survey approach was employed to gather data and 30 vocational high school English teachers completed a questionnaire measuring familiarity with ESP, conceptual knowledge, perceived competence, attitudes and reported teaching practices. The results reveal that teachers are highly aware of ESP and they have a common idea about its need-analysis and field-specific orientation. Teachers in general also show the favorableness of attitudes to ESP and interest, feeling has to update their professional competence. However, this positive attitude is somewhat not realized in classroom. Although a large number of teachers claim to functionally include materials and vocabulary specific to the area, significant ESP elements such as systematic needs analysis, real material development or involvement with professionals in the industry are irregularly utilized. These results indicate that the ESP implementation in vocational schools is still an ad hoc practice and not systematic support through the curriculum. It is recommended to improve esp teachers’ conceptual understanding of esp and their practical classroom work by enhancing teacher development, instructional materials, and institutional correspondences.